EFFECT OF WORKLOAD, COMPENSATION AND EMPLOYEE COMMITMENT TO THE EMPLOYEES PERFORMANCE OF PUBLIC WORKS AND SPATIAL ARRANGEMENTS OFFICE OF KARIMUN DISTRICT - Almansa Fitra, Mohamad; Indrayani, Indrayani; Andykhatria, Andykhatria; Syahril, Syahril; Hutasoit, Hasudungan; Wayan Catra Yasa, I (RADJA PUBLIKA, 2022)
This study aims to determine and describe how the influence of professionalism in managing village assets, optimizing the use of village assets and empowering the community so that it contributes to increasing village original income. The type of data used in this research is quantitative data. The data source in this research is secondary data. The object of this research is Kuala Sempang Village, Seri Kuala Lobam District, Bintan Regency. The results showed that the professionalism of village asset management had no significant effect on village original income, the optimization of the village assets utilization had a significant positive effect on village original income and community empowerment had no significant effect on village original income. So, in this study from the three variables only one variable has a significant positive effect on the village's original income. This study aims to analyze the influence of workload, work experience and work motivation on employee performance. The type of research used in this study is associative research. The method that can be used in this study is to use structural equation modeling (SEM) analysis based on variance, namely Partial Least Square (PLS). SEM with variance-based PLS so that it is able to handle two conditions, namely conditions with unspecified factors and conditions where the solution is unacceptable. This study uses computer smart program PLS 3.3.3. The population of this study is Civil Servants in the Public Works and Spatial Planning Office of Karimun Regency which amounts to 66 employees. The research data was collected by questionnaire instrument. The test results hypothesized the direct influence of workload with employee performance showed insignificant negative results (inner weight = -0.302, p = 0.149) so it can be concluded that the results of the study rejected hypothesis 1 because there is an insignificant influence between workloads on employee performance. The test results of the hypothesis of direct influence of work experience showed insignificant positive results (inner weight = 0.062, p = 0.717) so it can be concluded that the results of the study rejected hypothesis 2 because there is an insignificant influence between work experience and employee performance. The test results hypothesized the direct influence of work motivation showed insignificant positive results (inner weight = 0.211, p = 0.308) so it can be concluded that the results of the study rejected hypothesis 3 because there is an insignificant influence between work motivation and employee performance. The results showed that 12.3% of employee performance variables were influenced by workload variables, work experience and work motivation while the remaining 87.7% were influenced by other variables.